Losses of phosphorus, potassium and nitrogen from horse manure left on the ground. (31st December 2022) - Aronsson, Helena; Nyström, Sofia; Malmer, Elsa; Kumblad, Linda; Winqvist, Camilla
ABSTRACT: In this five-month Swedish field study, we examined losses of nutrients from horse manure over time, in order to examine how regularly manure should be cleared from paddocks in order to minimise the risk of nutrient leaching. Small heaps of manure (400 g) were placed in open cylinders outdoors and samples (five replicates) were taken on 12 occasions from December 2020 to May 2021. The samples were analysed for weight, dry matter content and concentrations of total nitrogen (N), ammonium N, total phosphorus (P), water-extractable P (WEP), potassium (K) and carbon (C). There was a fast decline in P and K concentrations and a strong correlation between accumulated precipitation and losses from the manure into the soil. The mean reduction in total-P was 11 mg P kg−1 manure dry weight per mm accumulated precipitation. Manure N was retained in the manure over the five-month period. In conclusion, this study demonstrated high mobility of P and K, indicating a need for strategies for rapid removal of manure from paddocks. Daily removal of manure from paddocks used year-round would, approximately, save 1.7 kg P and 5.5 kg K per horse per year, which could be recycled to replace non-renewable mineral fertilisers.